Effect of Vitamin D Supplementation in a Sample of Type 2 Diabetes Patients from Karak Governorate in Jordan - Hammouh, Fadwa Ghazi; Tukan, Salma Khalil; Takruri, Hamed Rabah (Pakistan Journal of Nutrition, 2015)
Vitamin D status of type 2 diabetes mellitus (T2DM) patients in Karak Governorate in Jordan was assessed and the relationship between vitamin D supplementation and blood glucose was found. The study recruited thirty three confirmed T2DM subjects (19 males and 14 females) with deficient or insufficient vitamin D status. They were given a supplement of 2000 IU of vitamin D3 daily for 1 month. Fasting blood samples were taken before and after supplementation. Serum levels of fasting blood glucose (FBG), glycosylated hemoglobin (HbA1c), calcium (Ca), insulin, parathyroid hormone (PTH) and 25 hydroxyvitamin D3 (25 (OH) D3) were determined and the homeostasis model assessment-insulin resistance (HOMA-IR), homeostasis model assessment-beta secretion (HOMA-beta) and quantitative insulin sensitivity check index (QUICKI) indices were calculated. The statistical analysis of experimental data indicates that there was a significant increase (p